CHIROPRACTIC DALAM PENDEKATAN HOLISTIK UNTUK NYERI DAN POSTUR: PERSPEKTIF DARI LITERATUR TERKINI - Mayduri Viola Anuersy; Abdullah, Dessy; Fitra Deny; Irma Primawati; Aryaldy Zulkarnaini (Nusantara Hasana Journal, 2025)
Chiropractic is a therapeutic method focusing on spinal manipulation to restore body balance, alleviate chronic pain, and improve posture. This approach is increasingly relevant in the modern era, characterized by sedentary lifestyles often leading to musculoskeletal problems. This article aims to review the current literature on the effectiveness of chiropractic care in managing pain and improving posture as part of a holistic healthcare approach. This study employs a systematic literature review method, analyzing 30 articles published between 2018 and 2024 from databases such as PubMed, ScienceDirect, and Google Scholar. The selected articles include clinical studies, reviews, and meta-analyses relevant to chiropractic care. The review results indicate that chiropractic care reduces lower back pain by up to 70% in patients with herniated discs. Furthermore, 85% of patients reported improved posture following chiropractic therapy over six months. Studies also noted that patients who combined chiropractic care with regular exercise experienced significant improvements in mobility and quality of life compared to those who only received chiropractic therapy. The analysis highlights that the benefits of chiropractic care extend beyond physical improvement, encompassing psychological aspects such as stress reduction due to chronic pain alleviation. Within a holistic approach, chiropractic contributes to overall body balance and promotes natural healing without invasive interventions. The discussion emphasizes the importance of integrating chiropractic care into modern healthcare systems, particularly as a preventive approach to address global health challenges stemming from sedentary lifestyles. Chiropractic care is an effective therapy for managing chronic pain and improving posture within a holistic healthcare context. This method not only offers physical benefits but also supports mental well-being, making it a promising non-invasive solution to enhance overall quality of life. Further research is necessary to explore the potential applications of chiropractic care in addressing other health conditions.